2021
DOI: 10.1016/j.ultsonch.2021.105638
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of β-carotene from pumpkin using switchable natural deep eutectic solvents

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(48 citation statements)
references
References 39 publications
0
48
0
Order By: Relevance
“…The process uses non-toxic, biodegradable solvents that do not affect the extracted extractant. As a result, the purification step of the extract can be omitted, and the extract can be directly used in food [16].…”
Section: Extraction and Sustainable Food Productionmentioning
confidence: 99%
“…The process uses non-toxic, biodegradable solvents that do not affect the extracted extractant. As a result, the purification step of the extract can be omitted, and the extract can be directly used in food [16].…”
Section: Extraction and Sustainable Food Productionmentioning
confidence: 99%
“…As an example of such an application, Sharma and Dash utilized a combined ANN and genetic algorithm (ANN-GA) approach for how to establish parameters for a DES-based microwave-assisted extraction process (microwave power, extraction time, liquid–solid ratio, and water percentage in DES) that allowed achieving a high extraction efficiency of phytochemical compounds from black jamun pulp [ 196 ]. Stupar et al applied the RSM and ANN model for the development of an optimized procedure for β-carotene ultrasound-assisted extraction from pumpkin using natural DESs [ 197 ]. Ghaedi et al described the development of linear and quadratic regression models for the prediction of CO 2 solubility in DESs and their aqueous solutions [ 198 ].…”
Section: Simulation Methods For Dessmentioning
confidence: 99%
“…Recently, an effective procedure has been developed for β-carotene extraction from pumpkins using DESs based on fatty acids [ 197 ]. To this end, the RSM and ANN approaches were used to optimize the extraction process.…”
Section: Main Directions Of Investigationsmentioning
confidence: 99%
“…It could reduce the possibility of oxidative damage [39]. The stability of other hydrophobic pigments such as -carotene in NADES was studied by Stupar et al, 2021. The authors reported that fatty acid NADES containing caprylic acidcapric acid (3:1) optimally extracted -carotene from pumpkin (96.74 g/mL).…”
Section: Stability Of Compounds In Nadesmentioning
confidence: 99%
“…-carotene from pumpkin in NADES has good stability if stored at 4 C. Hydrogen bonding interactions between solute and solvent molecules and pH are related to the stability of carotene in solution [42].…”
Section: Stability Of Compounds In Nadesmentioning
confidence: 99%